The influence of abusive leadership on organizational commitment: The mediating role of work stress - Khusniatun, Khusniatun; Azizah, Siti Nur (Jurnal Mantik, 2025)
This study aims to analyze the influence of abusive leadership on commitment organization with stress work as variable mediation. The study is based on the phenomenon of low loyalty of low attachment employees to the organization, which is suspected strongly influenced by style leadership that is not supported as well as height level stress work. In the context of cooperative save borrow in the sub-district Pituruh, pressure poor work, and interpersonal relationships between superiors and subordinates become issues crucial that affect the stability organization. Study This uses an approach with technique census against 44 employees. Data collection was carried out using a questionnaire, and data analysis using Structuralx EquatioCon Modeling (SEM) method with tool help SmartPLS version 4. Based on the analysis of the results, abusive leadership is proven own influence positively significant to stress Work with a coefficient of 0.514, t-statistic 5.217, p-value of 0.000. Furthermore, abusive leadership also has an effect significant to commitment organization with a coefficient of -0.274, t-statistic of 2.501 and a p-value of 0.013. Stress Work proved influential negative significant to commitment organization with a coefficient of -0.426, t-statistic of 3.505, and p-value of 0.001. In addition, stress Work mediates the influence of abusive leadership on commitment organization in a way significant with an indirect effect of -0.219, a t-statistic of 2.873, and a p-value of 0.004. Findings This contribution is important in the development theory exchange, as well as becoming a reference practical for organizations to form a climate of healthy and supportive work? loyalty employees